Historical evidence of glyphosate exposure from a US agricultural cohort - Melissa J. Perry; Daniele Mandrioli; Fiorella Belpoggi; Fabiana Manservisi; Simona Panzacchi; Courtney Irwin (BMC, 2019)
Abstract In response to the recent review by Gillezeau et al., The evidence of human exposure to glyphosate: A review, Environmental Health 1/19/19, here we report additional glyphosate biomonitoring data from a repository of urine samples collected from United States farmers in 1997-98. To determine if glyphosate exposure could be identified historically, we examined urine samples from a biorepository of specimens collected from US dairy farmers between 1997 and 98. We compared samples from farmers who self-reported glyphosate application in the 8 h prior to sample collection to samples from farm applicators who did not report using glyphosate. Of 18 applicator samples tested, 39% showed detectable levels of glyphosate (mean concentration 4.04 μg/kg; range:1.3-12) compared to 0% detections among 17 non glyphosate applicator samples (p-value < 0.01). One of the applicator samples that tested positive for glyphosate also tested positive for AMPA. Concentrations of glyphosate were consistent with levels reported in the prior occupational biomonitoring studies reviewed by Gillezeau et al. Accurately detecting both glyphosate and AMPA in this small sample of Wisconsin farmers demonstrates a) glyphosate exposures among farmers were occurring 20 years ago, which was prior to the widespread planting of genetically engineered glyphosate tolerant crops first approved in 1996; and b) liquid chromatography tandem mass spectrometry (LC-MS/MS) can be used for sensitive characterization in cryopreserved urine samples. These data offer an important historical benchmark to which urinary levels from current and future biomonitoring studies can be compared.